Berbagi Pengetahuan dan Motivasi Kerja terhadap Perilaku Inovatif Karyawan - Anggraini, Shela; Mansyur, Anwar (Oikonomia: Jurnal Manajemen, 2024)
This study aims to determine the effect of sharing knowledge and work motivation on employee innovative behavior. This study uses sampling techniques by purposive sampling method, determination of sampling is taken based on the desired amount. There were 104 respondents studied samples. The stages of this test consist of instrument tests, model tests and hypothesis tests using SPSS 23. Based on the results of the study shows that sharing knowledge and work motivation has a positive and significant effect on innovative behavior. With sharing knowledge and work motivation can make employees can create and implement a new idea that is creative and innovative, so that it can add insight.